BRAIN FUNCTION BASED DECEPTION DETECTION TECHNIQUES IN FORENSIC INVESTIGATIONS (Journal of Forensic Medicine & Toxicology, 2013)
A lie is considered to be said when it helps one to save his self-esteem or avoid punishment, and thereby helps to conceal the truth. Suspects lie just because they want to conceal their deeds/actions. Therefore, we require an instrument that would assist the examiner to find out if the accused concerned is telling a truth or lie. Efforts have been made to develop methods so that the effects of such manipulations can be detected using which one can infer that deception has been made. Traditionally, for this purpose, the Polygraph/Lie-detection test has been used. The lie-detection test measures the autonomic variables such as respiration, heart rate, pulse rate, blood pressure, and skin resistance of a suspect while he is being questioned. Other methods of physiological measurement, such as EEG, psychological tests, analysis of facial expressions, body movements, and evaluation of voice have been developed into techniques, which can reflect the presence of deception or lying in a subject. The validity of all these techniques remains a matter of constant debate. Recent advances in technology have enabled direct observation of the activities of the human brain during various cognitive operations, including lying. Measuring changes in the brain associated with detection of familiarity with units of information drawn from a crime scenario, which is known only to the perpetrator has shown potentiality to identify the perpetrator. Deception requires conscious manipulation of the truth recalled, which in turn results in the use of increased utilization of resources in the brain, whereas the truth could have been expressed with minimum utilization of such resources. Yet another method that is developed does not depend on either detection of familiarity or deception but on retrieval of originally acquired experiential knowledge of participation without requiring expression of such retrieved information.
Keywords: Polygraph; Brain Fingerprinting; BEOS; fMRI